Improving The Scientific Learning Outcomes Of Students Through Applicationquantum Lesson Learning Methods In Class Vwatu-Watu State Elementary School, Bombana Regency - Sumarni Sumarni; Chairan Zibar L.Parisu; Ashari Usman (Jurnal Sultra Elementary School, 2021)
The research problem in this study is: How can science learning outcomes be improved by applying the Quantum Teaching learning method in fifth-grade students of SD Negeri Watu-Watu, Bombana Regency? The purpose of this research is to determine how to improve science learning outcomes by applying the Quantum Teaching method in fifth-grade students of SD Negeri Watu-Watu, Bombana Regency. The background of this study includes: (1) students tend to play during the learning process, (2) low interest and learning outcomes, (3) teachers have not applied learning models that can foster students’ interest in learning, (4) lack of teacher creativity in teaching, and (5) limited student involvement during lessons.This research is a collaborative Classroom Action Research (CAR) conducted in two cycles, consisting of planning, implementation, observation, evaluation, and reflection stages. The subjects of this study were 23 fifth-grade students of SD Negeri Watu-Watu, consisting of 12 female and 11 male students. The results showed that: (1) the average student learning outcome in the first cycle was 76.40, increasing to 82.61 in the second cycle. The percentage of students achieving mastery learning increased from 60.87% (14 students) in the first cycle to 86.96% (20 students) in the second cycle. (2) Teacher activity improved from 81.58% in the first meeting of cycle I to 88.16% in the second meeting, and from 90.79% to 97.37% in cycle II. (3) Student learning activity improved from 76.32% in the first meeting of cycle I to 85.53% in the second meeting, and from 92.11% to 96.05% in cycle II. These findings indicate that the application of the Quantum Teaching method effectively improves science learning outcomes among fifth-grade students at SD Negeri Watu-Watu, Bombana Regency.